(3cJGH GdcQI hGdESWhGfIs - (3GQTejOSs
(3ChdgG (B:s
(3Cbhd HYO JMejO Gddg JYGdi Efi cfJ ai WdH Gdhbha Ydi HYV GdeSGFd GdePchQI ai cJGH GdcQI hGdESWhGfI s
(3BNQgG (B:s
(3afSHI eQHY GdbWQ Edi SMW GdOGFQI hfSHI KeGfjI hYTQjf Edi GKfjf hYTQjf Hd fSHI CQHYI YTQ hPdc eGCQOfGg hgPG JeGe Gdbhd ai JcHjQ GdOGFQI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdSGOS YTQs
(3HgG CTcGd gfOSjIs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1452s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdQjGVjGJs